Effect of nanoparticles on heat transfer in heat exchangers - Mahrooghi, Ali; Moghiman, Mohammad (Ciência e Natura, 2015)
In this paper, forced convection flow and heat transfer of a Al2O3/Water nanofluid have beeninvestigated numerically by single and two phase (volume of fluid) models. Nanofluid flows inside the innertube of the isothermally concentric circular and sinusoidal double tube heat exchangers while hot pure waterflows in the outer tube. The single-phase and two-phase models is used to simulate the nanofluid forcedconvection of 2% and 3% volume concentrations. The renormalization group k-ε model is used to simulateturbulence in ANSYS FLUENT 15.0. Results show that the overall heat transfer coefficient increases withnanoparticle volume concentrations in the heat exchangers. The highest overall heat transfer coefficient rates aredetected, for each concentration and shape, corresponding to the highest flow rate for the sinusoidal tube heatexchanger . The maximum overall heat transfer coefficient enhancement is 220% for the particle volumeconcentration of 3% at the inner tube of concentric sinusoidal double tube heat exchanger corresponding to flowrate =10 LPM. The results reveal that the Al2O3/water pressure drop along the inner tube of circular andsinusoidal double tube heat exchanger increases by about 3% and 5% for volume concentrations of 2% and 3%,respectively, given flow rate compared to the base fluid.Comparison of these results with Rohit S. Khedkar‘spublished experimental data, showed good agreement.